The long-read assembly of Apareiodon sp., a neotropical fish with a ZZ/ZW sex chromosome system - Wolf, Ivan Rodrigo (2024)
This study was supported by FAPESP (Fundação de Amparo à Pesquisa do Estado de São Paulo, grant number: 2015/16661-1), Fundação Araucária (Fundação Araucária de Apoio ao Desenvolvimento Científico e Tecnológico do Estado do Paraná, grant number: 9/2017), CAPES (Coordenação de Aperfeiçoamento de Pessoal de Nível Superior – Finance Code 001), and CNPq (Conselho Nacional de Desenvolvimento Científico e Tecnológico, grant number: 313566/2023-2). The authors are also grateful to Instituto Chico Mendes de Conservação da Biodiversidade (ICMBio, license number 15117) for authorizing the collection of specimens.